PEMETAAN KABUPATEN/KOTA DI PROVINSI JAWA BARAT BERDASARKAN NILAI UJIAN NASIONAL SMA DAN AKREDITASI SEKOLAH - Charles E. Mongi (Sam Ratulangi University, 2014)
ABSTRAK Pendidikan memiliki peranan yang sangat penting bagi setiap individu mulai dari usia dini sampai usia lanjut. Jenjang pendidikan terdiri dari jenjang pendidikan dasar, menengah dan tinggi. Penelitian ini membahas posisi relatif kabupaten/kota di Provinsi Jawa Barat terhadap nilai UN dan akreditasi sekolah menengah atas dan penggerombolan sekolah di Provinsi Jawa Barat. Hasil analisis biplot menghasilkan tujuh kelompok sekolah. Kelompok pertama berada di rata-rata nilai UN dan akreditasi. Kelompok kedua cenderung rendah pada nilai UN dan akreditasi. Kelompok ketiga rendah pada nilai UN. Kelompok empat tinggi pada nilai akreditasi. Kelompok lima tinggi pada nilai UN. Kelompok enam cenderung tinggi pada nilai UN eksak. Kelompok tujuh rendah pada nilai UN dan akreditasi. Kata kunci: Nilai UN, Akreditasi, Biplot Â MAPPING SENIOR HIGH SCHOOL IN WEST JAVA BASED NATIONAL EXAMINATION VALUE AND SCHOOL ACCREDITATION ABSTRACT Education has important role for individuals from childhood to the elderly. Educational levels consists primary education, secondary education and higher education. This study discussed the relative position of the districts in West Java Province throughout the national examination and high school accreditationas as well school clustering in West Java Province. Result of biplot analysis generated seven groups, first group were in the average national examination and accreditation. Second group were inclined low in national examination and also accreditation. The third group has a low national examination scores. The fourth group had a high score on the value of accreditation. Fifth group had a high value on national examination scores. The sixth group had inclined high national examination scores especially in science subjects. The seventh group had a low value on national examination and accreditation scores. Keywords: National Examination value, Accreditation, Biplot